1992
DOI: 10.1182/blood.v80.3.795.795
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and analysis of in vivo expression of murine P- selectin

Abstract: P-selectin (CD62) is a rapidly inducible cell surface adhesion molecule that is expressed on platelets and endothelial cells and mediates their interaction with leukocytes. In vitro studies have suggested that this receptor may play an important role in hemostasis and in inflammatory response to tissue injury. We report the molecular cloning and sequencing of murine cDNA for P-selectin. The lectin, epidermal growth factor (EGF)-like, transmembrane, and cytoplasmic domains are highly conserved between mouse and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(26 citation statements)
references
References 0 publications
2
22
0
2
Order By: Relevance
“…Certainly, another mechanism by which LPS promotes acute lung inflammation is by upregulating the expression of CAMs. Thus, the transcript levels of P-selectin, E-selectin, ICAM-1 and VCAM-1 are augmented in the lung, with peaks observed at 3-6 h after exposure to LPS (Sanders et al, 1992;Fries et al, 1993;Beck-Schimmer et al, 1997;Panes et al, 1999). In keeping with these studies, we found that i.t.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Certainly, another mechanism by which LPS promotes acute lung inflammation is by upregulating the expression of CAMs. Thus, the transcript levels of P-selectin, E-selectin, ICAM-1 and VCAM-1 are augmented in the lung, with peaks observed at 3-6 h after exposure to LPS (Sanders et al, 1992;Fries et al, 1993;Beck-Schimmer et al, 1997;Panes et al, 1999). In keeping with these studies, we found that i.t.…”
Section: Discussionsupporting
confidence: 86%
“…The lung tissue samples were obtained at 4 h postchallenge. This time point for measurements of CAM's mRNA was selected from previous reports (Sanders et al, 1992;Fries et al, 1993;Beck-Schimmer et al, 1997). Total RNA was extracted from lung tissue homogenates by using TriPure Isolation Reagent (Roche Applied Science, Indianapolis, IN, U.S.A.).…”
Section: Lps-induced Lung Inflammationmentioning
confidence: 99%
“…Endothelial selectins are not constitutively expressed, with the exception of E-selectin in the cutaneous microcirculation (Norton et al, 1991). Thus, the capacity of LPS to upregulate P-and E-selectin expression in vivo (Gotsch et al, 1994;Labow et al, 1994;Mayadas et al, 1993;Sanders et al, 1992) could explain the inhibitory eect of monoclonal antibodies (mAbs) against these molecules on LPS-induced neutrophil recruitment. It is not known, however, whether selectins are similarly required for neutrophil accumulation induced by a directacting in¯ammatory mediator such as a CXC chemokine.…”
Section: Introductionmentioning
confidence: 99%
“…From there it can rapidly be brought to the cell surface after exposure to thrombin, histamine, complement 5a, Ca 2ϩ ionophores, or adenosine diphosphate (21)(22)(23)(24). In mice, endotoxin injection has also been shown to induce P-selectin expression in liver, heart, lung, and kidney (25). Surface P-selectin expression is downregulated by internalization, degradation, and to a smaller extent by shedding into the plasma (22,24).…”
mentioning
confidence: 99%